Corporate social responsibility (CSR) and Islamic banks: a synthesis of literature review - Mohd Sofian, Fatimah Noor Rashidah; Muhamad, Rusnah (2016)
In the past 30 years, Islamic banks have developed tremendously across the various countries. Currently, challenges occurring in the global financial market operations have affected the development of Islamic banking practice.Key reports in the field have suggested that CSR activities are important in tackling this issue. Although the literature pertaining to CSR activities is extensive, the insights emerging from this to date have been limited.Whilst it is acknowledged that there are various dimensions to the study of CSR, including exploring CSR practices, the CSR concept, the CSR framework, CSR measurement, CSR dimension, CSR relationships, CSR impact and CSR determinants, the primary focus of this paper is to explore CSR practices.The findings from the current literature have found that CSR activities are not at a satisfactory level. The present paper will suggest that CSR activities should be integrated with Islamic and conventional elements in accordance with Shariah principles under the ‘Urf (customs) principle.It is expected that integrated CSR activities will attract practitioners to improvise current CSR strategies.It is suggested in addition that such a move would improve knowledge of CSR and Islamic banking in the academic world.